The educational research limits: pedagogical abstractionism and the field fragilities - Samuel Mendonça; Romualdo Portela de Oliveira; Kelly Cristina Leandro (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2019)
The object of this article is the educational research. Question: Do the pedagogical abstractionism and the educational field fragilities are barriers to consolidating the Education as science? The educational abstractionism concept is detailed by Jose Mário Pires Azanha's perspective, as well as the educational field fragilities are presented from Bernardete Gatti's studies. With this theoretical framework and taking into consideration this article's hypothesis that concerns the educational field disregard as science by the federal agencies: Coordination for Higher Education Staff Improvement - CAPES and National Council of Scientific and Technological Development - CNPq, we look for to affirm the rigor necessity in the education researches. As results, it is necessary to establish clear references regarding the education epistemological statute so a greater dialogue with other scientists from other sciences can be obtained. The Education defended with rigor will be able to access more financing, given the relation among the resources applied in each area and the democratic spaces dedicated to science construction representativity.